A New Nanocatalytic Spectrophotometric Assay for Cationic Surfactant Using Phosphomolybdic Acid-Formic Acid-Nanogold as Indicator Reaction - 蒋治良 覃惠敏 梁爱惠 (Chinese journal of chemistry, 2012)
In the pH 7.4 Na2HPO4-NaH2PO4 buffer solution, the cationic surfactant （CS） interacted with nanogold particles （NG） to form NG aggregations （NGA） that resulted in its color changing from wine red to blue-violet. NG has a strong catalysis on the formic acid-phosphomolybdic acid （PMo） colored reaction, but that of the NGA catalysis is weak. With the increase of CS concentration, the NGA increased and the NG decreased, the catalysis decreased and the absorption value at 700 nm decreased linearly. The concentrations of 6.25-250 nmol/L tetradecyl dimethyl benzyl ammonium chloride （TDBAC）, 0.625-250 nmol/L cetyltrimethyl ammonium bromide （CTMAB） and 12.5 -500 nmol-L 1 dodecyldimethylbenzyl ammonium chloride （DDBAC） had good linear responses to the decreased absorption value （AA70o nm）, with molar absorption coefficients of 2.2 × 106, 2.1 × 106 and 9 ×105 Lomol 1.cm 1 respectively. This method was simple, highly sensitive and low-cost.